Respuesta :

The simplified form of given expression is [tex]2x^3-5x^2-17x+20[/tex]

Solution:

Given that we have to simplify the expression

Given expression is:

[tex](x-4)(2x^2+3x-5)[/tex]

We can simplify the expression by multiplying each term in first bracket with each term term in second bracket

[tex]\rightarrow (x-4)(2x^2+3x-5)[/tex]

[tex]\rightarrow (x)(2x^2)+(x)(3x)+(x)(-5)-4(2x^2)-4(3x)-4(-5)[/tex]

Simplify the above expression by multiplying the numbers in each term and adding the coefficients of like variables in each term

[tex]\rightarrow 2x^3+3x^2-5x-8x^2-12x+20[/tex]

Combine the like terms

[tex]\rightarrow 2x^3+3x^2-8x^2-5x-12x+20[/tex]

[tex]\rightarrow 2x^3-5x^2-17x+20[/tex]

Thus the expression is simplified